Rehydration of corn grain with acid whey improves the silage quality - Rezende, Adauton V.; Rabelo, Carlos H. S. [UNESP]; Veiga, Rosane M.; Andrade, Luiz P.; Haerter, Carla J. [UNESP]; Rabelo, Flavio H. S.; Basso, Fernanda C. [UNESP]; Nogueira, Denismar A.; Reis, Ricardo A. [UNESP] (Elsevier B.V., 2014)
Our objective was to investigate the effects of rehydration with acid whey or water at three moisture levels, as well as the effects of bacterial inoculation, on the fermentation, chemical composition and aerobic stability of corn grain silages. The trial was conducted in a completely randomized design with four replicates in a factorial arrangement as follows: 3 (rehydration with three different moisture levels: 300,350 and 400 mL/kg of corn grain)x 2 (silage inoculated with bacteria or not inoculated (control))x 2 (liquid used in the rehydration: acid whey or water). Overall, corn grain silages rehydrated with acid whey produced more lactic acid than the silages rehydrated with water (13.8 vs. 12.6 g/kg of dry matter (DM), respectively). In addition, increases in the rehydration of corn grain silages promoted decreases (linear) in lactic acid concentration as well as in production of total acids. Although inoculated silages had higher pH as consequence of the rehydration using water at the three levels, these treatments presented high DM recovery. In general, neutral detergent fiber (aNDFom) decreased if inoculant was applied in corn grain silages rehydrated with acid whey. After silos opening, silages rehydrated with 350 or 400 mL/kg (independent of the liquid) had lower aerobic stability than silages rehydrated with 300 mL/kg. Overall, we found that the inoculant did not promote significant changes in the composition of the corn grain silage. In contrast, the potential of the use of acid whey in ensiling corn grain is high, as its addition leads to improvements in the fermentation process and aerobic stability of the silages. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Environmental sustainability; Fiber; Lactic acid bacteria; Water